Evaluation of the hygienic quality and nutritional value of traditional Lebanese “Kishk”, a dried fermented goat milk product - Salameh C.; Hosri C. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
“Kishk” is a traditional fermented milk, highly appreciated in Lebanon for its extended shelf life. It is a dried mixture of yogurt and bulgur, prepared essentially with goat milk, while sometimes cow milk could be used alone or mixed with goat milk. A survey has been carried out among forty Kishk producers in four Lebanese regions and samples were collected to assess their microbiological, chemical and organoleptic quality. The survey results showed that Kishk ingredients and the production techniques used differ significantly among Lebanese regions (type of milk and cereals) and according to the culinary traditions of people there. Microbiological results showed that samples fall within the Lebanese Kishk standards for Salmonella and coliforms, whereas a high contamination with Staphylococcus aureus and anaerobic bacteria was recorded in the samples produced with caprine milk collected from the South of Lebanon. Finally, sensory assessment showed that Kishk produced in the South received the highest score for color, which is strongly related to the use of brown bulgur there.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)